The differences of Candida sp. colonization profiles in the sputum of lung cancer and pulmonary tuberculosis patients - Sofiana Anis Sahara; Noorhamdani; Etty Fitria Ruliatna (Journal of Clinical Microbiology and Infectious Diseases, 2021)
Background: The fungal infection is a worldwide health problem triggered by the increasing number of antibiotic and immunosuppressant drug usage, indwelling catheter procedures, and immunocompromised patients. Lung fungal infection is a disease caused by colonization or the fungal infection hypersensitivity reaction. Lung cancer and lung tuberculosis (TB) are chronic diseases that can lead to an immunocompromised state and induce the colonization of Candida sp in the respiratory tract. Patients contracted with these diseases tend to colonize Candida sp. in their respiratory tract, which may develop to pulmonary candidiasis with worse prognostic. Thus, this study aimed to understand the difference of Candida sp colonization profile in the sputum of Lung cancer and lung TB patients. Method: This study was an observational study with a cross-sectional approach using 60 consecutively determined samples, where 30 samples were from each lung cancer and lung tuberculosis group. The data were analyzed by using SPSS 25 sav. For numeric variables, we used unpaired t-test analysis, meanwhile the categoric variables such as the laboratory, microscopic, and sputum culture test results; and compared the result statistically using Chi-Square analysis to compare the Candida sp colonization profile in both groups. Results: We found that 80% of the lung cancer patient and 87% of lung TB patients had positive results on Candida sp culture, which is dominated by Candida albicans. We observed higher WBC value and hyphae of Candida in the lung TB patient group. There was a significant difference in the sensitivity of Candida albicans isolate against Amphotericin B, and non-Candida albicans isolate against Fluconazole and Micafungin in the lung cancer and lung TB patients group. The sensitivity value of Gram assessment was 40% with 90% specificity. Conclusion: Candida albicans were mostly found among lung cancer and lung TB patients. There were significant differences in the WBC value and antifungal sensitivity test results in Candida albicans isolates against Amphotericin B and non-Candida albicans isolates against Fluconazole and Micafungin in lung cancer lung TB patients.